Effects of Panax ginseng and ginsenosides on oxidative stress and cardiovascular diseases: pharmacological and therapeutic roles - Sun Hee Hyun; Kiran D. Bhilare; Gyo In; Chae-Kyu Park; Jong-Hoon Kim (Journal of Ginseng Research, 2022)
Traditionally, Asian ginseng or Korean ginseng, Panax ginseng has long been used in Korea and China to treat various diseases. The main active components of Panax ginseng is ginsenoside, which is known to have various pharmacological treatment effects such as antioxidant, vascular easing, anti-allergic, anti-inflammatory, anti-diabetes, and anticancer. Most reactive oxygen species (ROS) cause chronic diseases such as myocardial symptoms and cause fatal oxidative damage to cell membrane lipids and proteins. Therefore, many studies that inhibit the production of oxidative stress have been conducted in various fields of physiology, pathophysiology, medicine and health, and disease. Recently, ginseng or ginsenosides have been known to act as antioxidants in vitro and in vivo results, which have a beneficial effect on preventing cardiovascular disease. The current review aims to provide mechanisms and inform precious information on the effects of ginseng and ginsenosides on the prevention of oxidative stress and cardiovascular disease in animals and clinical trials.